Optimizing maize Production: Balancing yield, quality, and economic benefits through planting density - Driven nutrient analysis - Zhen Wang; Yanan Guo; Ruizhi Xie; Keru Wang; Guoqiang Zhang; Peng Hou; Jun Xue; Shang Gao; Dongping Shen; Liang Fang; Linli Zhou; Lirong Sun; et al. (Journal of Agriculture and Food Research)
This study aimed to explore the possible changes in the contents of grain nutritional components and test weight when increasing maize yield by increasing planting density, and how to address the impacts of these changes on maize supply and demand. A two-year field experiment was conducted in Tongliao, Inner Mongolia Autonomous Region from 2020 to 2021. Using drip irrigation with integrated water and fertilizer technology, the experiment involved two maize hybrids, Dika 159 (DK159) and Xianyu 335 (XY335), at six planting densities (6.0, 7.5, 9.0, 11.5, 12.0, 13.5 × 104 plants per hectare). Research indicators included grain yield, test weight, the contents and yields of protein, starch, oil, and fiber, as well as the test weight of these four nutrients. Results showed that a reasonable increase in planting density could boost yield by 0.26–2.93 t ha-1. Although there were significant differences in test weight among treatments, all were first-grade test weight maize. Increasing planting density significantly increased starch and oil contents, and while it reduced protein content, the yields of the four nutrients increased significantly with higher grain yield and peaked at the highest grain yield. The protein test weight decreased significantly with increased density, while the starch test weight first increased and then decreased. Compared with traditional test weight-based pricing, the new maize pricing model developed in this study can better balance growers' production benefits and processing enterprises' quality requirements, providing a feasible approach to optimize maize production and enhance overall benefits.